Micronuclei Frequency In Normal, Potentially Malignant And Malignant Epithelium Using Special Stains – A Comparative Study - KHARABE, Dr. Juhi Soni, Dr.Halima Zakir, Dr.Tarique Ansari, Dr. Namrata Suthar, Dr. Ashish Pillania, Dr. Satish Chandra (Drugs and Cell Therapies in Hematology, 2021)
To compare the Micronuclei frequencies in oral normal, potentially malignant and malignant epithelial cells using three different stains, i.e Feulgen stain, Papanicolaou stain (PAP) and Hematoxylin and Eosin stain (H and E), the present study was carried out on 100 patients in the Department of Oral and Maxillofacial Pathology and Microbiology, Shree Bankey Bihari Dental College, Ghaziabad. Results revealed that the frequency of micronuclei was significantly higher with Papanicolaou stain in potentially malignant lesions. Thereby, micronuclear assay can be used as a biomarker of genotoxicity in predicting the effects of cancer progression.